RESULT OF APPLICATION OF THE IMPROVED COMPLEX THERAPY OF TREATMENT OF ATOPIC DERMATITIS FOR A CHILD 6 - Іщейкін, К.Є. (World of Medicine and Biology, 2012)
In the article the features of clinical motion of atopic dermatitis are presented for children, that require the individual going near diagnostics and treatment of this disease taking into account a form, stage, to weight of skin defeat, presence of respiratory symptoms of atopy, concomitant diseases, age of patients, state them immune system. The high degree of therapeutic efficiency of the offered improved complex therapy is well-proven.